"Globalisation, governance reforms and development in India/ edited by Kameshwar Choudhary" - "Choudhary, Kameshwar(ed.)" (London, 2007)
Globalisation has brought forth significant changes in India and has generated intense discussion about the national level economic reforms that it has brought in. In the process, the state level reforms have not received much attention. This book is an attempt to fill in this gap. It brings together contributors from different disciplines and presents a contemporary analysis of globalisation, governance reforms and development in India and covers the theoretical and conceptual spectrum, state level reforms, and the social, cultural and political dimensions of globalisation and reforms in the country.
Keywords: India - Economic conditions - 21st century